Silent threat in early pregnancy: A case of spontaneous heterotopic pregnancy with tubal rupture - Oktama, Nizan Dani; Fakhrizal, Edy (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Heterotopic pregnancy (HP) is a rare but potentially life-threatening condition characterized by the coexistence of intrauterine and extrauterine pregnancies. While its incidence in natural conception is estimated at 1 in 30,000 cases, the risk increases considerably with the use of assisted reproductive technologies. Because its symptoms often mimic those of ectopic pregnancy, HP remains a diagnostic challenge, particularly in patients without recognized risk factors. Purpose: To highlight the silent yet serious threat of spontaneous heterotopic pregnancy in early gestation, illustrated by a case of tubal rupture in a natural conception. Method: A descriptive case report of a 43-year-old multigravida woman who presented at 7 weeks of gestation with sudden lower abdominal pain and clinical features of intra-abdominal hemorrhage. Diagnostic evaluation included ultrasonography and laboratory investigations, followed by an emergency laparotomy. Results: Ultrasound imaging revealed two intrauterine gestational sacs along with free fluid in the pouch of Douglas. Laboratory tests indicated anemia (hemoglobin 8.1 g/dL) and marked leukocytosis. Emergency laparotomy confirmed a ruptured right fallopian tube with massive intraperitoneal bleeding. The patient underwent right salpingectomy, left tubectomy, and intrauterine curettage at her request. Her postoperative recovery was uneventful, and she was discharged in good condition after two days. Conclusion: This case underscores the diagnostic difficulty of heterotopic pregnancy in spontaneous conceptions. The presence of an intrauterine pregnancy may create false reassurance, masking a concurrent ectopic gestation. Clinicians should consider HP in the differential diagnosis of any reproductive-aged woman with abdominal pain, regardless of conception method, to prevent life-threatening maternal complications.